Integrating Team Game Tournament Cooperative Learning Model and Kokami Media to Foster Arabic Speaking Abilities - Saepurrohman, Aep; Yunus, Badruzzaman M; Musthafa, Izzuddin; Sunarya, Yaya; Ummah, Wardatul; Setiawan, Ridwan (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This research addresses the challenges faced by class X-2 students at Madrasah Aliyah Al-Jawami Cileunyi, Bandung, characterized by low proficiency in speaking Arabic. This issue stems from students’ perception that Arabic is difficult and monotonous, compounded by the limited use of diverse teaching media during Arabic instruction. To overcome this, the researcher applied a cooperative learning model of the Team Game Tournament (TGT) type, incorporating Kokami media. The study aimed to evaluate students’ Arabic speaking skills before and after implementing this model and to analyze the level of improvement achieved. In this study using a quasi-experimental one-group pre-test and post-test design, the findings revealed that students’ initial speaking skills were low. However, after employing the TGT model with Kokami media, their speaking skills improved significantly, reaching an average score of 76.85, categorized as good (70-79). The improvement rate of 0.05 or 50% indicates a moderate enhancement level. These results underscore the effectiveness of integrating cooperative learning with engaging media in improving speaking skills. The study implies that innovative teaching strategies can address motivational and skill-related barriers in language learning. Future research should explore the long-term effects of similar models, adapt them for other language skills, and investigate their application in diverse educational contexts to refine further and generalize these findings.